Germany's Economic Unification. An Assessment after Ten Years - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2000)
A political miracle occurred when Germany was reunited, and at first glance an economic miracle has followed. Real incomes in the east have now reached the western level, and investment per capita has been much higher than in the w est. However, every third deutschmark spent in the east has been coming from the west, investment in equipment has fallen below the west German per capita level, and convergence seems to have come to a halt at an overall labor productivity of only 55% of west Germany. Excessively high wages coupled with investment incentives that made the cost of capital negative rank high among the possible explanations. This paper describes reforms of the labor market that could help to make convergence continue.
Keywords: 330